Cardiovascular reactivity and prediction of the high blood pressure in the community. - Mikhail Benet Rodríguez; Liliana J Espinosa Chang; Juan José Apollinaire Pennini; Milagros L León Regal; María Felicia Casanova González (Medisur)
Background: The development of strategies to reduce the prevalence of high blood pressure is an important challenge for all countries, populations, and governments. For this reason, the search of method in the prediction of the high blood pressure is an appropriate way, and a very important objective to get. Objetive: This study expects to show that cardiovascular hyperreactivity determined by the sustained weight test is a predictor of the high blood pressure independently from other cardiovascular risk factors. Methods: A five year cohort study was carried out (from 1998 to 2003) in which two groups were created. The 1st one with CHR (n = 41) and the 2nd one with (n= 127) of cardiovascular normoreactivity (CNR). Variables such as cardiovascular hyperreactivity high blood pressure, obesity, family history of high blood pressure, body mass index rate, smoking habit, salt consumption and alcohol consumption. An evaluation of the HBP risk was performed in each group, and the values of incidence of high blood pressure in each of them were compared. The chi square test was used as a statistic method. The stratified analysis and the determination of relative risk with a confidence interval of the 95 percent. The statistical significance was 95%. Results: The incidence of hypertension in the cohort of HRC was of 34,15/100 people and in the CNR of 10,24/100 people chi square = 13,3 GL= 1 P= 0,007, on the other hand, when we made adjustments according to different cardiovascular risk markers to determine the relationship between hypertension and hyperreactivity, it was observed that the relationship exists in spite of the risk marks mentioned before. Conclusions: The individuals whit HRC determined by the SWT have a risk to develop higher significant sustained hypertension then the cardiovascular normorreactivos ones this is an evidence that this method is useful to predict HBP.